ANALYSIS OF FACTORS AFFECTING PUBLIC INTEREST IN USING INTERNET SERVICE PROVIDERS IN BATAM CITY - Johny Budiman; Darvin Ang (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Research conducted by researchers in this paper is to identify factors influencing the willingness to pay of Batam residents to use the internet service providers. Materials used in this study are : convenience, price, value, quality, trust, and willingness to pay more. Trust will be the mediator variable for the connection between the dependent factor of wilingness to pay more with the rest of the variable. The sample used in this research are resident of the Batam City who is using the the internet service providers provided in batam city. A sample of 284 respondents was used in this research. Data is collected using the Smart Partial Least Square (PLS) app. The results of the study showed that the influence variable which was stated to be significantly positive on willingness to pay more are quality and convenience. Variables that are declared insignificant are the effect of price and value.